Analisis Pengaruh Investasi Swasta dan Pengeluaran Pemerintah Daerah Terhadap Pertumbuhan Ekonomi dan Kemiskinan di Provinsi Jambi - Siti Aminah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2016)
This study aimed to analyze the effect of private investment and local government spending to economic growth and poverty in Jambi Province. Research using time series data from 1985 to 2012 year. The analytical tool used is regression by the method of